Pengaruh Kebijakan Dividen Dan Bi Rate Terhadap Nilai Perusahaan Dengan Struktur Modal Sebagai Variabel Intervening - Apriana, Ifan; Akhmadi, Akhmadi (Fakultas Ekonomi Universitas Gresik, 2023)
This study aims to examine the effect of dividend policy and the BI Rate on firm value with capital structure as an intervening variable in banking sector companies. The approach used in this research is a quantitative approach. The sample in this study were 14 banking sector companies listed on the IDX in the period 2018 - 2022. The research data is secondary data which is then analyzed using the panel regression analysis technique. The results of this study are that the dividend policy and the BI Rate cannot directly affect firm value, the level of dividend policy and the BI rate do not always have an impact on the level of firm value, but indirectly, policy and the BI Rate can affect company value. company through capital structure. Capital structure is a full mediation on the effect of dividend policy and firm value.